THE PHRASEOLOGY OF PUBLIC INTERNATIONAL ENGLISH - Howarth, Peter (International Journal of English Studies, 2009)
In Howarth 2002 a limited amount of data was presented for preliminary analysis of the phraseology of international press conferences. Tliat study focused on the distinction between spontaneous and scripted spoken English and examined whether these styles of speech could be correlated with differences in phraseological performance. The current study broadens the scope of this research and aims to investigate in more detail the nature of the language used in public international settings between native- and non-native speakers. It will draw on a corpus of approximately 2.5 million words of transcribed press conferences, containing large numbers of exchanges between native and non-native spokespeople and journalists. ’The press conferences have been conducted during the last eight years in Former Yugoslavia and have the common subject matter of peace-keeping and security. In addition to using a variety of corpus analyses (e.g. keywords, recurrent word combinations, fixed phrases), the study will attempt to deepen our understanding of this genre.